Refining relational climate conversations to promote collective action - Julia C. Fine (npj Climate Action, 2024)
Abstract Many US residents are worried about the climate crisis, but few are involved in collective climate action. Relational climate conversations are a commonly recommended yet understudied means of encouraging action. This study examines the effects of conversations between US climate activists and non-activists they knew, most of whom were concerned about climate change. Non-activists reported increased knowledge, perceived efficacy, and intention to take action following the conversations, but did not participate in collective climate action more than control groups. Common barriers included low perceived efficacy, lack of knowledge about collective climate action, and psychological distance of action. Activists’ discussion of collective climate action was correlated with an increase in perceived efficacy among non-activists. Because perceived efficacy has been found to predict collective action, these results suggest that focusing on action, more so than solutions in the abstract, could enhance the effectiveness of relational climate conversations.